2013
DOI: 10.2319/012413-75.1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of three hygienic protocols in reducing biofilm adherence to removable thermoplastic appliance

Abstract: Objectives: To examine the ability of a removable thermoplastic appliance (RTA) to adsorb hygienic solutions and inhibit bacterial growth and to examine the efficacy of three hygiene protocols in reducing bacterial biofilm adherence to RTA. Materials and Methods: Solution adsorption and bacterial growth inhibition were examined in vitro using paper vs RTA discs. Subsequently, 11 patients treated with RTA (mean age, 29.1 6 4.7 years) were assigned into a sequence of three hygiene protocols: regular RTA brushing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 22 publications
0
34
0
4
Order By: Relevance
“…Since the forming procedure always includes a heating cycle of either vacuum forming or pressure forming, it might cause distinct changes in their morphologic and mechanical properties. Furthermore, thermoplastic materials under intraoral use eventually undergo thermal, mechanical, and chemical degradation, and these changes can be observed through molecular structure and orientation (Schuster et al, 2004;Shpack et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Since the forming procedure always includes a heating cycle of either vacuum forming or pressure forming, it might cause distinct changes in their morphologic and mechanical properties. Furthermore, thermoplastic materials under intraoral use eventually undergo thermal, mechanical, and chemical degradation, and these changes can be observed through molecular structure and orientation (Schuster et al, 2004;Shpack et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the CHX and vibrating bath with cleaning solution hygiene protocols significantly ( P <0.001) reduced baseline biofilm adherence, by 16% and 50% respectively, with the vibrating bath with cleaning solution treatment found to be three times more efficient than CHX. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Los pacientes deben recibir un protocolo de higiene regular no solo de sus piezas dentales, sino también del dispositivo alineador, en el cepillado se debe utilizar cualquier pasta dental que contenga fluoruro alrededor a los 1400 ppm (19).…”
Section: Cuidadosunclassified
“…El paciente debe cepillar el alineador con un cepillo de dientes cada noche, y luego sumergirlo en un enjuague bucal de clorhexidina durante 15 minutos, para posteriormente lavarlo con agua y volver a colocarlo en la boca (19). EFECTIVIDAD La efectividad de los alineadores Invisalign es discutible, para algunos esta se da simplemente si se lleva a cabo la reducción interproximal según lo prescrito, pero no se hacen otras modificaciones para aumentar el movimiento del diente; esta percepción limitada de efectividad no es aceptada por todos, y a decir verdad podría no ser considerada como un buen indicador.…”
Section: Cuidadosunclassified